2011
DOI: 10.1002/eji.201041360
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33 induces skin inflammation with mast cell and neutrophil activation

Abstract: Psoriasis is a common chronic autoimmune condition of the skin characterized by hyperplasia of epidermal keratinocytes associated with pro-inflammatory cytokines. IL-33 is a new member of the IL-1 superfamily that signals through the ST2 receptor and was originally defined as an inducer of T helper 2 (Th2) cytokines. Recently, broader immune activatory potential has been defined for IL-33 particularly via mast cell activation and neutrophil migration. Here, we show that ST2 À/À mice exhibit reduced cutaneous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
123
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(142 citation statements)
references
References 40 publications
13
123
3
3
Order By: Relevance
“…These reports indicated that accumulated neutrophils in liver were significantly associated with PBC progression. In addition, IL-33 has been shown to induce neutrophil migration to the inflammatory tissues Verri et al 2010;Hueber et al 2011), a finding consistent with our current data which suggested that serum from PBC patients induced more neutrophils to migrate compared to HC. These results indicated that the overexpression of IL-33 in the liver, at least in part, contributes to the accumulation of neutrophils.…”
Section: Discussionsupporting
confidence: 92%
“…These reports indicated that accumulated neutrophils in liver were significantly associated with PBC progression. In addition, IL-33 has been shown to induce neutrophil migration to the inflammatory tissues Verri et al 2010;Hueber et al 2011), a finding consistent with our current data which suggested that serum from PBC patients induced more neutrophils to migrate compared to HC. These results indicated that the overexpression of IL-33 in the liver, at least in part, contributes to the accumulation of neutrophils.…”
Section: Discussionsupporting
confidence: 92%
“…In mast cells, activation of IL-33R, either alone or simultaneously with FcεRI, leads to, or enhances, the production of TNF-α, IL-6, IL-13, MCP-1, MCP-3, and MIP-1α via the Src and MAPK cascade [49]. This activation mirrors enhanced in vivo mast cell response in a mast cell dependent model of psoriasis [50] and airway inflammation [51]. Indeed, IL-33 is highly expressed in asthmatics [52] …”
Section: Il-33r Signaling and Modulation Of Fcr Activationmentioning
confidence: 94%
“…Moreover, IL-33 production of IL-13 independently of Fc«RI stimulation (Ho et al, 2007) stimulated prostaglandin D 2 , but not tryptase, release from activated human MCs . IL-33 was also able to prime murine MCs for enhanced activation by IgG immune complexes (Drube et al, 2010;Kaieda et al, 2012), and stimulated MC-dependent neutrophil influx (Hueber et al, 2011;Enoksson et al, 2013). In addition to activation through cross-linking of the highaffinity IgE receptor (Fc«RI) (Blank and Rivera, 2004), MCs are also stimulated by a variety of other triggers (Theoharides et al, 2007), such as the neuropeptide neurotensin (Donelan et al, 2006) and substance P (Zhang et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%